A brief analysis of the possibility of unschooling as a methodological proposal for integral education for homeschooling in Brazil (Research, Society and Development, 2021)
Unschooling is a homeschooling methodology well-known in the United States, but not widespread in Brazilian territory. The purpose of this article is to analyze the unschooling methodology and compare it to the description of integral education by various authorities on the subject, and the integral education booklets of the Ministry of Education, and to validate it (or not) as a comprehensive education proposal. for home education in Brazil. For this, in the methodology, the basic work of the founder of the method, John Holt (Holt & Farenga, 2017), among others, will be analyzed, in which he explains what is unschooling and its practice, and concepts of integral education will be described and examined, in the context Brazilian, in order to examine not only the feasibility of the aforementioned teaching method at home, but also its effectiveness in the full reach of the student, in the affective, cognitive and psychomotor dimensions. As a result of the research, it was found that unschooling is a homeschooling methodology that reaches all dimensions of the student, fully serving as a type of comprehensive education in Brazil.